Photodegradation mechanisms and kinetics of Eosin-Y in oxic and anoxic conditions. (October 2017) - Alvarez-Martin, Alba; Trashin, Stanislav; Cuykx, Matthias; Covaci, Adrian; De Wael, Karolien; Janssens, Koen
Abstract: Lakes based on Eosin-Y are extensively used by 19th century artists. Unfortunately, the identification of these pigments in paintings is a difficult task because Eosin-Y degrades very fast under the influence of light. The characterization of the (photo)degradation products of Eosin-Y can be very useful for the identification of these pigments in historic works of art and related cultural heritage artifacts. Furthermore, knowledge on how different factors influence the discoloration process (e.g. different types of irradiation sources and presence/absence of oxygen) is a valuable tool for preventive conservation. To this aim we performed a study on the photodegradation of Eosin-Y in solution under different illumination and in both oxic and anoxic conditions. The photodegradation of Eosin-Y was monitored by UV-VIS spectrophotometry, LC-QTOFMS and electrochemistry techniques. Results indicated higher degradation rates, by a factor of 20 or higher, under illumination with wavelengths near to the main absorbance band of the red pigment. Two different degradation pathways are observed under the conditions studied. LC-QTOFMS and electrochemistry suggested that in the presence of oxygen the degradation mechanism is an oxidative process where the breakdown of the structure causes the total discoloration. Meanwhile under anoxic conditions, a debromination process takes place while the chromophore, and consequently the color of the molecule in solution, remains essentially intact. Highlights: The discoloration of Eosin is strongly dependent on the absence/presence of oxygen. Different degradation rates are observed under the different irradiation wavelengths employed. The kinetics fit to first and pseudo-first order under oxic and anoxic conditions. Under oxic conditions the discoloration is attributed to the chromophore breakdown. Under anoxia a sequential debromination process is ascribed to the degradation.